Kärkkäinen's spirit and salvation: A female pentecostal appraisal. Issue 4 (4th September 2020) - Urvas, Sanna
Abstract: Spirit and Salvation is the fourth volume of a constructive theology series by Professor Veli‐Matti Kärkkäinen. It is a continuation of Kärkkäinen's impressive scholarship in Pneumatology and offers a fine example of his inclusive methodology. Especially important and informative is the section regarding spiritual powers and cosmology, which provides for an ecumenical audience a healthy understanding of demonic powers. Experience is one epistemological factor in Kärkkäinen's work, which is observed through methodology. An alternative way to approach theological method, from the female pentecostal perspective, which regards experience as important, is offered as an option or a continuation to Kärkkäinen's scholarship.